2009
DOI: 10.1387/ijdb.082846yc
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting old vaginal topics: conversion of the Mllerian vagina and origin of the "sinus" vagina

Abstract: Vaginal development has been a longstanding controversy, which hampers studies on vaginal diseases as well as cervical and uterine diseases. Most concerns center on: why is the vaginal epithelium different from the uterine epithelium; and where does the vagina originate from? It is commonly held that the rodent vagina has a dual origin: the cranial part is derived from the Mullerian duct (Mullerian vagina) and the caudal part derived from the urogenital sinus (sinus vagina). This concept was deduced from morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 120 publications
1
39
1
1
Order By: Relevance
“…It has been a commonly held belief (based on murine studies) that the vagina is of dual origin. The Müllerian ducts form the cranial portion, the so-called "Müllerian vagina", while the urogenital sinus is the origin of the caudal portion, the so-called "sinus vagina" as reviewed by Cai [38] and Kurita [39]. However, based on murine studies Cai [38] concluded that the recent evidence supports a Müllerian duct origin for the entire vagina.…”
Section: Genes Responsible For Development Of the Vaginamentioning
confidence: 99%
See 4 more Smart Citations
“…It has been a commonly held belief (based on murine studies) that the vagina is of dual origin. The Müllerian ducts form the cranial portion, the so-called "Müllerian vagina", while the urogenital sinus is the origin of the caudal portion, the so-called "sinus vagina" as reviewed by Cai [38] and Kurita [39]. However, based on murine studies Cai [38] concluded that the recent evidence supports a Müllerian duct origin for the entire vagina.…”
Section: Genes Responsible For Development Of the Vaginamentioning
confidence: 99%
“…The Müllerian ducts form the cranial portion, the so-called "Müllerian vagina", while the urogenital sinus is the origin of the caudal portion, the so-called "sinus vagina" as reviewed by Cai [38] and Kurita [39]. However, based on murine studies Cai [38] concluded that the recent evidence supports a Müllerian duct origin for the entire vagina. More recent cell lineage tracing studies in humans have demonstrated that the Wolffian ducts, Müllerian ducts, and the urogenital sinus all play integral roles during the formation of the human vagina in a caudal to cranial manner [40].…”
Section: Genes Responsible For Development Of the Vaginamentioning
confidence: 99%
See 3 more Smart Citations